Opinion article: Neurosurgical treatment for neuro-ophthalmologic conditions - Williams, Zoe R.; Lee, Andrew G.; Fraser, Clare L.; Falardeau, Julie; Subramanian, Prem S.; Chen, John J.; Al Othman, Bayan; Dinkin, Marc J.; Mollan, Susan P.; Al-Zubidi, Nagham; Vates, Edward (Frontiers in Ophthalmology, 2023)
A significant role of the neuro-ophthalmologist is to counsel patients on appropriate management and anticipated visual prognosis for conditions affecting the afferent and efferent visual systems, including those requiring neurosurgical treatment. However, the literature regarding anticipated neuro- ophthalmologic prognosis after neurosurgical intervention for cerebral aneurysms, sellar lesions, optic pathway tumors, and elevated intracranial pressure is limited with many key questions unanswered. For example, if a cerebral aneurysm is equally amenable to clipping or endovascular coiling, is there a preferred approach in terms of visual prognosis based on aneurysm location? Is dural venous sinus stenting (VSS) for idiopathic intracranial hypertension (IIH) superior, equivalent or inferior to shunting in terms of visual recovery and safety profile? Landmark studies on pituitary tumors using pre-operative optical coherence tomography (OCT) imaging of the optic nerve head to predict visual recovery after surgical decompression of the optic chiasm have changed neuro-ophthalmologic practice and enabled patients to be better informed regarding expected visual outcomes. 1,2 In order to optimize an interdisciplinary team approach to patient care, further studies of visual outcomes for neuro- ophthalmologic conditions requiring neurosurgical intervention are needed.